The effect of self efficacy on daily living activities in post non hemorrhagic stroke patients - Nur Djohim, Fadhilah Arofah; Istiqomah, Siti; Lahdji, Aisyah (South East Asia Nursing Research, 2024)
A non-hemorrhagic stroke occurs due to obstruction or blockage that causes the brain to lack oxygen, which can lead to death, disability, and paralysis. Post-stroke patients often feel insecure about their disabilities, so they have limitations in socializing and carrying out daily activities. However, this can be overcome if the patient has self-efficacy, an aspect of the health belief model. This study aimed to determine the effect of self-efficacy on daily living activities in post-hemorrhagic stroke patients. This study is a quantitative study in the form of an analytical study using a cross-sectional research design with samples that meet the inclusion and exclusion criteria of 80 respondents at RSUD KRMT WongsonegoroSemarang with the consecutive sampling technique. Data were taken using a questionnaire instrument which was then tested with the help of computer software. The majority of respondents had a high self-efficacy of 56 (70%), and the majority had independent daily living activities of 32 (40%). The analysis used in this study was the Spearman rank test on the self-efficacy variable, with a value of p = 0.00 and r = 0.709. It was found that there was a significant influence between self-efficacy and activity of daily living in post-hemorrhagic stroke patients, the higher the self-efficacy, the higher the ADL.